The intentions to get vaccinated against influenza and actual vaccine uptake among diabetic patients in Ningbo, China: identifying motivators and barriers - Lixia Ye; Ting Fang; Jun Cui; Guanghui Zhu; Rui Ma; Yexiang Sun; Pingping Li; Hui Li; Hongjun Dong; Guozhang Xu (Human Vaccines & Immunotherapeutics, 2021)
Background: Health authorities recommend influenza vaccination to diabetic patients. Nevertheless, the vaccination coverage of adults was low in China. This study aimed to estimate influenza vaccination intentions and actual uptake among diabetic patients in China and identify the motivators and barriers associated with vaccination. Methods: During Nov 2016–Jan 2017, 1960 diabetic patients were invited to participate in the investigation about influenza vaccination based on health belief model (HBM). To link vaccination intention to behavior, a follow-up survey was conducted to collect vaccination records of the 2016–2017 season. Predictors of the motivation to obtain influenza vaccination were assessed using logistic regressions. Results: 1914 diabetic patients completed the survey. 46.13% participants reported intentions to be vaccinated against influenza and 7.84% actually received vaccination. In the multivariate models, while all the domains of HBM constructs were associated with intentions, age, increasing numbers of comorbidity, urban residents, perceived susceptibility, perceived benefits, free vaccination, and vaccination history displayed positive associations with vaccine uptake while increasing income and perceptions of barriers were negative predictors of vaccine uptake. Besides, interactions between perceived susceptibility and healthcare workers’ (HCW’s) recommendation, perceived severity and benefits, perceived severity and health-seeking behaviors, perceived benefits, and influence of family/friends had a significant positive effect modification on the vaccine uptake. Conclusion: To improve diabetic patients’ influenza vaccination and close the intention-behavior gap, multipronged strategies are required not only to increase vaccination intention by promoting HCW’s recommendation to improve perceptions about influenza vaccination but also facilitate a follow through on initial intentions by implementing free influenza vaccination program funded by the government.